2015
DOI: 10.1016/j.jtcvs.2014.08.072
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation as a bridge to lung transplantation in the United States: An evolving strategy in the management of rapidly advancing pulmonary disease

Abstract: Short-term survival with the use of extracorporeal membrane oxygenation as a bridge to lung transplantation has significantly improved over the past few years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
87
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(92 citation statements)
references
References 31 publications
4
87
1
Order By: Relevance
“…Cystic fibrosis patients had the best survival, with a 56% survival rate at 3 years from the initiation of ECMO. This was contrary to the report by Hayanga and colleagues (25). Toyoda and colleagues (33) reported a 77% success rate in 31 patients who were bridged with ECMO.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Cystic fibrosis patients had the best survival, with a 56% survival rate at 3 years from the initiation of ECMO. This was contrary to the report by Hayanga and colleagues (25). Toyoda and colleagues (33) reported a 77% success rate in 31 patients who were bridged with ECMO.…”
Section: Discussioncontrasting
confidence: 59%
“…Because old age increases the risk of perioperative mortality, older patients should be approached with caution. The report by Hayanga and colleagues (25) showed that age greater than 35 years was an independent risk factor in patients who were bridged. Nonetheless, a follow-up case report and literature review described a successful transplantation for a 70-year old patient who was bridged with conscious sedation and no mechanical ventilation (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…transplantation, but with the improved safety profile of modern ECMO, several groups have demonstrated excellent outcomes with the use of pre-transplant extracorporeal support [27][28][29][30][31]. In some circumstances, VV ECMO via a dual lumen cannula can provide sufficient gas exchange to allow for the removal of mechanical ventilatory support for patients awaiting lung transplantation.…”
mentioning
confidence: 99%
“…Initial studies after the inception of LAS scoring noted that one-year outcomes in patients with higher LAS (17) and patients bridged with ECMO were lower (18,19). However, more recent studies analyzing the UNOS database have showed that outcomes in ECMO patient's post-lung transplant may be similar to non-ECMO patients, especially in centers with higher transplant volumes and experience (20,21).…”
Section: Introductionmentioning
confidence: 99%